ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMILIHAN KARIR GENERASI Z (STUDI KASUS PADA MAHASISWA HOTEL AND TOURISM BUSINESS UNIVERSITAS CIPUTRA SURABAYA) - Satrio, Celine Brian; Budidharmanto, Lexi Pranata (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2020)
The purpose of this study is to determine the factors that influence the career choice decisions of Ciputra University Hotel and Tourism Business students. This type of research used quantitative research. The population applied is the alumni of Ciputra University students class 2011-2015. The sample taken was only student alumni of the 2013-2015 class, because the three generations were included in the Generation Z class. The total sample was 65 respondents with the type of work as an intrapreneur. The data were collected using a questionnaire measured by a Likert scale. This study used confirmatory factor analysis with the help of SPSS 26 and processed 16 existing variables. The data test used is validity test, reliability test, and factor analysis. Based on the results of the study, it is concluded that there are 4 factors that influence the career choice decisions of Hotel and Tourism Business students, namely factors of working conditions and environment, prospects and duration of work, intrinsic value and work contribution, conditions and flexibility of working time. For further research using the same theme, it is recommended to reconsider other influencing factors such as adding other variables so that the research will be better.Keywords: Career Selection Decisions, Generation Z, Factor Analysis